1998
DOI: 10.1016/s0960-9822(98)70443-9
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog signaling is essential for hair development

Abstract: Shh signaling is not required for initiating hair follicle development. Shh signaling is essential, however, for controlling ingrowth and morphogenesis of the hair follicle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
542
1
7

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 694 publications
(582 citation statements)
references
References 37 publications
32
542
1
7
Order By: Relevance
“…In E17.5 wild-type epidermis few Ptch1 (Figure 1b In order to define the spatio-temporal distribution of Hh signalling activity during HF development we quantitated the Ptch1 and Gli1 transcript density along the proximal-distal length of HFs at different stages of the HF cycle. Previous studies have shown that Hh signalling is dispensable for HF initiation and hair germ development (stage 2) (Chiang et al, 1999;St-Jacques et al, 1998). Consistent with these findings, we observed low levels (90% (Figure 3a, c, e and g) concurrently exhibit decreased e-cadherin (Figure 3b and f), p120-catenin (Figure 3d and h) and ZO-1 (data not shown) expression.…”
Section: Resultssupporting
confidence: 92%
“…In E17.5 wild-type epidermis few Ptch1 (Figure 1b In order to define the spatio-temporal distribution of Hh signalling activity during HF development we quantitated the Ptch1 and Gli1 transcript density along the proximal-distal length of HFs at different stages of the HF cycle. Previous studies have shown that Hh signalling is dispensable for HF initiation and hair germ development (stage 2) (Chiang et al, 1999;St-Jacques et al, 1998). Consistent with these findings, we observed low levels (90% (Figure 3a, c, e and g) concurrently exhibit decreased e-cadherin (Figure 3b and f), p120-catenin (Figure 3d and h) and ZO-1 (data not shown) expression.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, mitotic cells, as detected via short term BrdU incorporation are mainly in the Ptch1 expressing region, raising the likelihood that Ptch1 expressing cells comprise the transit amplifying population, and possibly the taste bud stem cells [33]. In both fungiform and circumvallate papillae, BMP4-ß-gal-expressing cells may lie adjacent to the Ptch1 expressing cells, or may express Ptc1 suggesting the possibility that BMP4 and SHH may coordinate taste cell turnover, as has been demonstrated for regeneration of a number of other epithelial appendages, including hair follicles [76,77]. …”
Section: Discussionmentioning
confidence: 99%
“…The hedgehog signalling pathway is one of the most fundamental signal transduction pathways in embryonic development, being responsible for patterning the developing neural tube, axial skeleton, limbs, lungs, skin, hair and teeth (Bellusci et al, 1997;Hardcastle et al, 1998;Marigo and Tabin, 1996;Riddle et al, 1993;St-Jacques et al, 1998). Much of what is known of the function of this pathway has been derived from studies in Drosophila, and many of the key elements have been conserved from¯ies through to humans Hahn et al, 1996a).…”
Section: Abstract: Patched; Hedgehog; Basal Cell Carcinomamentioning
confidence: 99%
“…In vitro studies suggest that each of these proteins can act through the same signal transduction pathway, and that the di erent hedgehog genes regulate patterning of di erent organ systems by virtue of their unique expression pattern (Echelard et al, 1993;Marigo et al, 1996;Stone et al, 1996). The most extensively studied of the vertebrate hedgehog genes is Shh which is expressed widely throughout the developing CNS, limb, lung, gut, teeth and hair-follicle (Bellusci et al, 1997;Hardcastle et al, 1998;Litingtung et al, 1998;Marigo and Tabin, 1996;Riddle et al, 1993;St-Jacques et al, 1998). Dhh and Ihh are primarily involved in development of the germline and skeletal system respectively (Bitgood et al, 1996;Vortkamp et al, 1996).…”
Section: Hedgehog Signalling Pathwaymentioning
confidence: 99%